Metal ions and nanomaterials for targeted bone cancer immunotherapy - Qin, Sen; Hu, YaoFeng; Luo, HuaSong; Chu, Wei; Deng, RuCui; Ma, JinLiang (Frontiers in Immunology, 2025)
Bone cancer remains a significant challenge in oncology, with limited success in current therapeutic approaches, particularly immunotherapy. Emerging research highlights the potential of integrating metal ions and nanomaterials for targeted immunotherapy in bone cancer. Metal ions, including calcium, magnesium, and zinc, play a significant role in modulating immune responses within the tumor microenvironment, affecting essential pathways necessary for immune activation. Meanwhile, nanomaterials, particularly metallic nanoparticles, offer precise drug delivery and immune system modulation, improving the efficacy of immunotherapeutic agents. This review explores the synergistic effects of metal ion-nanomaterial conjugates, discussing their role in enhancing immune cell activation, particularly T-cells and macrophages, and their potential for controlled drug release. We highlight preclinical advancements in bone cancer treatment using metal ion-responsive nanoparticles, and address current challenges such as biocompatibility and toxicity. Finally, we discuss the future prospects of these technologies in personalized and precision medicine, aiming to revolutionize bone cancer immunotherapy.